Assessing pain in rabbits: how well does the Rabbit Grimace Scale work in the veterinary practice?. (2nd July 2020) - Shaw, Danielle; Parkes, Jessica; Reynolds, Helen
Abstract : Background: Pain recognition in rabbits ( Oryctolagous cuniculi ) can be a challenging task for the registered veterinary nurse (RVN) and can often result in the delivery of suboptimal nursing care if pain goes undetected. Although the Rabbit Grimace Scale (RbtGS) can assist in pain assessment, it is a tool that is currently underutilised in practice. Aims: The aim of this research was to evaluate the efficacy of the RbtGS to assess if it is useful in the veterinary practice to improve rabbit welfare standards. Methods: 31 individuals, 25 student veterinary nurses and six RVNs participated, taking RbtGS scores for 19 rabbits through either live or video observations. The rabbits were either healthy or experiencing a pre-existing illness or health condition as assessed by a veterinary surgeon. Results: The RbtGS scores indicated that the majority of participants were unable to accurately identify the rabbits most likely to be in pain, suggesting that it may not be an optimal tool in rabbit pain assessment. However, RVNs who had more experience in practice were better at identifying signs of pain and stress in the rabbits. Conclusion: Experience and ongoing education is invaluable to improve rabbit care. There is a need for a veterinary rabbit pain score system in order to standardise pain management across species.